ANALISIS KARYA GAMBAR ILUSTRASI SISWA KELAS VIII DI SMP NEGERI 2 BERASTAGI DITINJAU DARI UNSUR-UNSUR SENI RUPA - John Febri Siahaan; Azmi Azmi (Universitas Negeri Medan, 2022)
AbstrakDrawing illustrations is one of the contents in the subjects of SBK (Cultural Arts and Skills) in junior high school. The process of drawing illustrations in junior high school for class VIII does not miss the principles of fine art, so it is important for teachers to convey clearly about what the principles are and how much role they play in the process of creating an illustration. The purpose of this research is to find out the illustration works of students of class VIII of State Junior High School 2 Berastagi quarantined in terms of fine art principles. The illustration images studied are in the form of flora objects with types of cartoon illustrations. The methods used in this study are qualitative descriptive methods. The population in this study all illustrated illustrations of students of class VIII-1 Of State Junior High School 2 Berastagi which amounted to 234 works. In this study the authors took samples using purposive sampling techniques. The reason for sampling is the number of illustration works included in the flora object that is flowers. In addition, the reason for sampling is time constraints due to shared health interests that do not allow all students to carry out the learning process as usual and the decision is sourced from the government. The results of illustration work from some students for example for the principle of composition, there are still students who put the dominating object on one side of the drawing field. The purpose of this research is to find out the illustration works of students of class VIII of State Junior High School 2 Berastagi quarantined in terms of fine art principles. The illustration images studied are in the form of flora objects with types of cartoon illustrations. The principles of fine art in the illustration works of students of grade VIII-1 of State Junior High School 2 Berastagi numbered as many as 20 works.Keywords: Works; Illustrated image; Principles of Fine Art AbstrakMenggambar ilustrasi merupakan salah satu muatan dalam mata pelajaran SBK (Seni Budaya dan Keterampilan) di SMP. Proses menggambar ilustrasi di SMP untuk kelas VIII tidak lepas prinsip-prinsip seni rupa, sehingga penting untuk guru dalam menyampaikan secara jelas tentang apa saja prinsip tersebut dan seberapa besar perannya dalam proses menciptakan sebuah gambar ilustrasi. Adapun tujuan penelitian ini adalah untuk mengetahui karya gambar ilustrasi karya siswa kelas VIII SMP Negeri 2 Berastagi ditinaju dari segi prinsip-prinsip seni rupa. Karya gambar ilustrasi yang diteliti yaitu berupa objek flora dengan jenis ilustrasi kartun. Adapaun metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Populasi dalam penelitianini seluruh karya gambar ilustrasi siswa kelas VIII-1 SMP Negeri 2 Berastagi yang berjumlah 234 karya. Dalam penelitian ini penulis mengambil sampel dengan menggunakan teknik purposive sampling. Alasan pengambilan sampel adalah jumlah karya ilustrasi yang termasuk dalam objek flora yaitu bunga. Selain itu alasan pengambilan sampel. adalah keterbatasan waktu karena kepentingan kesehatan bersama yang tidak memungkinkan seluruh siswa melaksanakan proses belajar seperti biasanya dan keputusan tersebut bersumber dari pemerintah. Hasil karya ilustrasi dari beberapa siswa misalnya untuk prinsip komposisi, masih ada siswa yang meletakkan objek yang mendominasi pada salah satu sisi bidang gambar. Adapun tujuan penelitian ini adalah untuk mengetahui karya gambar ilustrasi karya siswa kelas VIII SMP Negeri 2 Berastagi ditinaju dari segi prinsip-prinsip seni rupa. Karya gambar ilustrasi yang diteliti yaitu berupa objek flora dengan jenis ilustrasi kartun. Prinsip-prinsip seni rupa pada karya gambar ilustrasi siswa kelas VIII-1 SMP Negeri 2 Berastagi yang berjumlah sebanayak 20 karya.Kata Kunci: Karya; Gambar Ilustrasi; Prinsip-Prinsip Seni Rupa